Mifepristone: an alternate to dinoprostone in induction of labour - R., Sailatha; M., Famida A.; Chellaiyan D., Vinoth Gnana; K., Vijayalakshmi; S., Sathiya; S., Renuka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To assess and compare the efficacy, safety and fetomaternal outcome of mifepristone versus dinoprostone in priming the cervix and in inducing labour in pregnant women at term. Methods: This is a prospective comparative study done in Chettinad health and research institute, over a period of one year from October 2015 to October 2016. 50 pregnant women (Group 1) in 3rd trimester with unfavorable cervix were given 200mcg of mifepristone orally. If labour did not start or if the Bishop score remained poor at the end of 24hrs, induction was continued with 0.5mg of dinoprostone gel at a maximum of 3 gels at 6th hourly interval. Another 50 pregnant women (Group2) in 3rd trimester underwent induction according to the routine dinoprostone gel regimen of maximum 3 gels at intervals of 6hrs. Results: Improvement in Bishop score was significant with mifepristone by the end of 24hrs.But, in comparison, there was statistically significant improvement in Bishop score in favour of dinoprostone (Mean 4.7) than mifepristone (Mean 4.0). Also, the induction delivery interval was significantly less (Mean 11.5 hrs) with dinoprostone than mifepristone (Mean 20.3 hrs). Number of cases undergoing LSCS for failed induction was less in mifepristone group (4%). The rate of vaginal delivery, Caesarean sections, instrumental delivery and overall fetal outcome was comparable in both groups. Conclusions: Mifepristone is a safe, effective and suitable alternate agent for cervical ripening and initiation of labour when given 24 h before onset of labour.